2009
DOI: 10.1080/10410230902805932
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Risk, Efficacy, and Anxiety in Smokers' Cancer Information Seeking

Abstract: Using the risk perception attitude (RPA) framework and the 2005 Health Information National Trends Survey data, this research investigated the role of perceived personal risk, perceived comparative risk, response efficacy, communication efficacy, and anxiety in smokers' active cancer information seeking. The RPA predictions on the interactions between perceived personal risk and the two efficacy measures were not supported. Perceived personal risk and response efficacy were associated with cancer information s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…15). Past studies have found relationships between increased health information-seeking behavior and higher self-efficacy, heightened health knowledge and proactivity, more visits to the physician, increased confidence talking with physicians, as well as decreased anxiety, fear, and stress (Lambert & Loiselle, 2007;Murray et al, 2003;Nicholson et al, 2005;Rimal, 2001;Zhao & Cai, 2009). Conversely, individuals who do not seek health information are less likely to engage in preventive behaviors (Ramanadhan & Viswanath, 2006) and tend to be individuals with lower levels of education and socioeconomic status (Murray et al, 2003;Ramanadhan & Viswanath, 2006).…”
Section: Health Information-seeking and Sourcesmentioning
confidence: 95%
“…15). Past studies have found relationships between increased health information-seeking behavior and higher self-efficacy, heightened health knowledge and proactivity, more visits to the physician, increased confidence talking with physicians, as well as decreased anxiety, fear, and stress (Lambert & Loiselle, 2007;Murray et al, 2003;Nicholson et al, 2005;Rimal, 2001;Zhao & Cai, 2009). Conversely, individuals who do not seek health information are less likely to engage in preventive behaviors (Ramanadhan & Viswanath, 2006) and tend to be individuals with lower levels of education and socioeconomic status (Murray et al, 2003;Ramanadhan & Viswanath, 2006).…”
Section: Health Information-seeking and Sourcesmentioning
confidence: 95%
“…27 While anxiety can support health information seeking for some people, it can be counter-productive in others. 28,29 Providing health information for the public may result in causing or alleviating anxiety. One study assessing the impact of a health information service on consumers identified that for most, providing health information reduced anxiety about a health concern, but in 10% it increased their anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The Risk Perception Attitude Framework is especially relevant to our investigation because it conceptualizes cognitive risk perceptions as a property of the individual and not as a property of the message, as in Witte's (1994) extended Parallel Processing Model. The Risk Perception Attitude Framework has also been used to predict health protective behaviors to protect against a variety of risks (Real, 2008;Rimal & Juon, 2010;Wong, 2009) as well as health related intentions Sullivan, Beckjord, Rutten, & Hesse, 2008), knowledge ) and information seeking (Real, 2008;Rimal & Juon, 2010;Turner, Rimal, Morrison, & Kim, 2006;Zhao & Cai, 2009). Most of these studies, particularly those using survey-based rather than experimental research, have provided at least some support for the model.…”
Section: Self-efficacy and Response Efficacymentioning
confidence: 96%
“…However, their results revealed that high-risk groups in general experienced more anxiety than did low-risk groups no matter what their efficacy levels were. Zhao and Cai (2009) took a slightly different approach and proposed that anxiety would mediate the effects of cognitive risk perception and efficacy on information seeking. Although the results of their study showed anxiety to be a weak mediator, the researchers demonstrated that anxiety was a direct predictor of information seeking, suggesting that emotions may have direct and independent effects on behavior.…”
Section: Self-efficacy and Response Efficacymentioning
confidence: 99%